Правове врегулювання статусу православної церкви у Польщі в період її автокефалізації ( 1919-1925 рр.) - Федін, М.І.; Федин, М.И.; Fedin, М. (My University, 2011)
The legal status of the Orthodox Church at Poland in the period of autocephalous' proclamation is examined. The basic articles of the Polish Constitution of 1921 and the provision of a "Temporary rules" that regulated the legal status of the Orthodox Church are analyzed. The speciﬁ city of the relationships between the Orthodox Church with a Polish state and the Moscow patriarchality during the autocephalous' execution is disclosed.
Федін М. И.Правове врегулювання статусу православної церкви у Польщі в період її автокефалізації ( 1919-1925 рр.) / М.І.Федін. //Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 12-18 . С. 332-340.
Keywords: Православна Церква; Правове положення Православної Церкви в Польщі; Польська Православна Церква; Православна Церква у Польщі в період її автокефалізації ( 1919 - 1925 рр. ); Православная Церковь в Подьше в период её автокефализации (1919 - 1925 гг. ); Польская Православная Церковь; Правовое положение Православной Церкви в Польше; Православная Церковь; Orthodox Church; The legal status of the Orthodox Church in Poland; Orthodox Church of Poland; The Orthodox Church in Podshe during her avtokefalizatsii (1919 - 1925 years.)